MENUMBUHKAN KESADARAN SEJARAH GENERASI MUDA MELALUI KEARIFAN LOKAL BUDAYA MELAYU DI KOTA MEDAN - Gading Kaizen; Pernando Oktavianus; Bintara Sirait; Arfina Amalia; Widya Widya (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
It is very important to educate the next generation about history. As for sharing historical records with the next generation, this project intends to investigate the indigenous wisdom of the Malay population. In-depth data collection from a thorough literature review is used in the qualitative approach of this research. The research findings reveal that efforts are being made to promote local history in society through teaching and cultivating interest in local historical stories. The capacity of the community to study, investigate, and be aware of local history in their area is greatly facilitated by the availability of accompanying facilities and infrastructure. In an effort to retain and preserve knowledge of historical records that have been lost or nearly forgotten, historical texts are used to validate the identification of groups of people. Since the past is the outcome and realization for the people of that time, historians and new generations are looking back at the past. Public interest in history is growing. Understanding history becomes even more important when technology and progress dominate society. Communities can interact with resource persons directly at this seminar or through publication activities, making it easier for the public to learn about local history, broaden their knowledge, and interact with others. Customs, beliefs, arts, traditions, traditional ceremonies, traditional clothing, regional food, social stratification, and other aspects of local culture can all be observed. This diversity is the result of how a group of people organize and adapt to their environment. The next generation will continue the established trend. Through publications and seminars, the public can interact directly with resource people to gain further knowledge and exchange information. In the era of globalization, Malay traditions such as poetry and gurindam need to be developed based on historical stories to preserve local culture.